2019
DOI: 10.1186/s13046-018-0995-9
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miRNA-214 in cancer-associated fibroblasts contributes to migration and invasion of gastric cancer cells through targeting FGF9 and inducing EMT

Abstract: BackgroundCancer-associated fibroblasts (CAFs), one of the principal constituents of the tumor microenvironment, have a pivotal role in tumor progression. Dysregulation of microRNAs (miRNAs) in CAFs contributes to the tumor-promoting ability of CAFs. However, the mechanism underlying the involvement of miRNAs in CAFs of gastric cancer (GC) is not fully understood. This study aimed to explore the effects of miRNA-214 in CAFs on GC migration and invasion.MethodsThe primary CAFs and corresponding normal fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(103 citation statements)
references
References 50 publications
2
97
0
Order By: Relevance
“…The tumor-promoting ability of CAFs is enhanced by microRNA dysregulation [254]. CAFs stimulate EMT in gastric cancer cells in a microRNA-214-dependent manner-it induces tumor-promoting ability of CAFs through fibroblast growth factor 9 (FGF9) targeting [255,256]. Likewise, suppression of microRNA-149 (through regulation of IL-6 levels) induces EMT, promoting protumor activity of CAFs [257].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…The tumor-promoting ability of CAFs is enhanced by microRNA dysregulation [254]. CAFs stimulate EMT in gastric cancer cells in a microRNA-214-dependent manner-it induces tumor-promoting ability of CAFs through fibroblast growth factor 9 (FGF9) targeting [255,256]. Likewise, suppression of microRNA-149 (through regulation of IL-6 levels) induces EMT, promoting protumor activity of CAFs [257].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…miRNAs have been reported to play crucial roles in tumor biological processes, including proliferation, apoptosis, migration, invasion, and differentiation (9). The association of non-coding RNAs especially miRNA dysregulation with the occurrence and development of cancer has been supported by evidence (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…While in bladder cancer miR-182-5p can regulate the expression levels of Smad4 and RECK, and high-expression of miR-182-5p can significantly shorten the overall survival of bladder cancer patients [11]. By regulate the expression of FGF9, miR-182-5p can probably induce malignant lesions by inducing Epithelial-Mesenchymal, cell proliferation and growth of tumor cells, as various studies have identified FGF9 participate in the tumor development such as gastric cancer [28], hepatocellular carcinoma [32], NSCLC [21] and so on. All these results indicated that as an important upstream regulator, miR-182-5p participate in the biology functions related to malignant lesions development.…”
Section: Discussionmentioning
confidence: 99%